2015
DOI: 10.11113/jt.v74.4669
|View full text |Cite
|
Sign up to set email alerts
|

Microprocessor-Based Athlete Health Monitoring Device based on Heart Rate and Stride Length Calculation

Abstract: Abnormal heart rate or low heart rate during exercise or recovery has been known to cause cardiac arrest and even sudden death in some cases.  Similarly, research has shown that low step rate while running may be the causal factor for running injuries due to the force impact exerted and the extra loadings on the lower body joints. Commercial electronic devices used by athletes typically use either accelerometers or coil springs to estimate the step rate resulting in low accuracy. This paper describes the desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
11
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(16 citation statements)
references
References 14 publications
4
11
1
Order By: Relevance
“…Similar values were reported in the literature with studies demonstrating step counting accuracies from 96% to 100% [11,25,26,28,29,30]. Moreover, in this study, the accuracy of step counting was more than 99% using cumulative sum without pre-set thresholds, which is an advantage compared to previous studies where the use of thresholds was necessary [11,26,28]. It is worth noting that most of the previous studies based the step count on pressure signal variation, for which a pre-set threshold is required [25,26,30,33].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Similar values were reported in the literature with studies demonstrating step counting accuracies from 96% to 100% [11,25,26,28,29,30]. Moreover, in this study, the accuracy of step counting was more than 99% using cumulative sum without pre-set thresholds, which is an advantage compared to previous studies where the use of thresholds was necessary [11,26,28]. It is worth noting that most of the previous studies based the step count on pressure signal variation, for which a pre-set threshold is required [25,26,30,33].…”
Section: Discussionsupporting
confidence: 91%
“…However, accuracy of step counts computed from the FSR H individual pressure-signal appeared to be less variable across walking speeds and settings. This may explain the preference for heel zone when only one FSR is used to determine step counts, as illustrated in a study by Bakhteri et al [28]. Although one study has shown that there was no difference of vertical ground reaction force across four foot types (normal foot, pes valgus, pes cavus and hallux valgus) [48], foot type can affect pressure signals and consequently detection of steps.…”
Section: Discussionmentioning
confidence: 99%
“…Data transmission methods were Bluetooth, wireless and wire modules with sampling frequencies varying from 10 Hz to 400 Hz (see Table 2 and Table 3). For step detection, instrumented insoles were validated using visual observation [25,31,34,35], other devices (the Runtastic pedometer application and other smartphone applications) [34,36], or using a predefined number of steps [24,36,37] (see Table 3). To validate the instrumented insoles for posture and activity recognition, comparisons were made between the smart insole data and that collected from direct observation during data collection or from a video recording or from other wearable devices (2D accelerometer (ADXL202), gyroscope (Murata, ENC-03J), ActivPAL device, PPAC (plantar-pressure based ambulatory classification) and FF (foot force sensor) + GPS [18,26,31,32,33,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60] (see Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…In eight articles, the setting was not mentioned [38,39,51,52,54,56,57,59]. For step counting, evaluations were also performed in both laboratory (n = 3) [25,31,35,37] and community (n = 2) [24,34] environments, but for shorter durations (2 min, [31] and 6 minutes [35]), on predefined distances of 16 meters [25] and 720 m [34] or for a predetermined number of steps (50 steps [36] and 100 steps [24,37]) as illustrated in Table 3.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation